Enhancing higher-order eigenmodes of AFM using bridge/cantilever coupled system. (November 2021) - Dou, Zhipeng; Qian, Jianqiang; Li, Yingzi; Lin, Rui; Wang, Tingwei; Wang, Jianhai; Cheng, Peng; Xu, Zeyu
Abstract: The wide application of multi-frequency atomic force microscopy (AFM) places higher demands on the higher-order modes response of the cantilever. The response of the higher modes however is generally weaker than that of the fundamental mode in air. Researchers have proposed many methods, most of which involve cantilever modification, to enhance higher-order eigenmodes response. These previous results are proved to be effective, but the microfabrication is expensive. In this article, we propose a novel model based on bridge/cantilever coupled system to enhance the higher-order modes response of AFM cantilever. The segmented beam model provides a new thinking to explain the appearance of undesired peaks in mode analysis of cantilever. Through theoretical analysis and simulation, we find that higher resonance modes are enhanced by tuning the bridge to match the high resonances of the single clamped cantilever. The length, thickness of the coupled system and the location of excitation can affect the enhancement. In summary, this model provides a new way to improve higher mode response for multi-frequency and other high bandwidth applications of AFM.